Multivariate Drought Frequency Analysis and Risk Assessment: A case study for Kahramanmaras Province - Musa Eşit; Mehmet İshak Yüce (Doğal Afetler ve Çevre Dergisi)
Drought is a natural disaster that occurs in nearly all climatic regions as a result of seasonal or longer-term lack of precipitation. Global warming, insufficient precipitation, low precipitation intensity and duration, low relative humidity and other factors all cause the prevalence of drought. In this study, multivariate drought frequency analysis and risk assessment of Kahramanmaras province were analyzed by using copula functions. After the drought parameters (duration and severity) were obtained by the SPI (Standardized Precipitation Index) method, the most appropriate marginal distributions were found for each parameter. Finally, depending on the appropriate marginal distributions, the conditional return probabilities and periods of the drought parameters of Kahramanmaras province were obtained after the most appropriate copula function was calculated. As a result of this study, the highest conditional return period of drought severity was observed in the center of Kahramanmaras, while the lowest return period was found in the district of Elbistan. Considering the highest conditional drought duration period, Afşin district has the highest return period (least risky), while Elbistan district has the shortest return period (risky). It has been observed that the province of Elbistan has a higher drought risk compared to other districts and the center of Kahramanmaras according to both the conditional drought severity and the drought duration return period. This study provides useful information to decision makers in the management of drought risk assessment for Kahramanmaras province.